A prospective study to assess role of serum lactate dehydrogenase in prediction of adverse outcomes of pre-eclampsia and eclampsia - Jharia, Jyoti; Mathur, Pooja; Dave, Anupama; Mathur, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy induced hypertension is one of the most dreaded complication in developing countries. The purpose of this study is to evaluate incidence, risk factors and complications of pre-eclampsia and eclampsia and its relation to serum LDH levels. This was done with a view to making recommendations towards furtherance of objectives of this initiative. Methods: 380 patients with diagnosed eclampsia and preeclampsia were included based on a proforma. Results: Higher grades of proteinuria, higher BP and serum LDH levels >600 IU/L are significantly associated with adverse maternal and fetal outcome. Conclusions: LDH co-relates with adversity of maternal and fetal outcome in eclampsia and pre-eclampsia.